Comparative Effectiveness of Microprocessor-Controlled and Carbon-Fiber Energy-Storing-and-Returning Prosthetic Feet in Persons with Unilateral Transtibial Amputation: Patient-Reported Outcome Measures. Issue 4 (October 2020) - Kaluf, Brian; Duncan, Ashley; Bridges, William
ABSTRACT: Introduction: Microprocessor ankles (MPAs) have recently been developed for persons with lower-limb amputation to overcome known limitations of fixed-ankle energy-storing-and-returning (ESAR) feet. This study aimed to examine differences in patient-reported balance, mobility, socket comfort, and preference between an ESAR foot and an MPA in persons with unilateral transtibial amputation (UTA). Materials and Methods: Twenty-three participants with UTA enrolled in an institutional review board–approved, randomized crossover protocol with ESAR (Pacifica LP) and microprocessor-ankle configurations (Kinnex, Freedom Innovations) and a 4-week accommodation period. The outcome measures collected included Activities Specific Balance Confidence Scale (ABC), Prosthesis Evaluation Questionnaire–Mobility Subscale (PEQ-MS), and Prosthetic Limb User Survey of Mobility (PLUS-M). Participants were asked to rate Socket Comfort Score (SCS) while ascending and descending a 15° sloped ramp. Finally, ankle-foot preference and aspects liked and disliked about each configuration were recorded. Results: Significant improvements were seen with the MPA in patient-reported mobility in the community (PEQ-MS, ρ = 0.0465) and socket comfort walking and standing on slopes (SCS, ρ < 0.001). Differences in balance confidence (ABC) did not reach a level of significance, whereas improvement in perceived mobility with a prosthesis approached a level of significance (PLUS-M, ρ = 0.102). When asked, 81% of participants preferred the MPA over the ESAR foot. Participants reported positively about the reduced weight of the ESAR foot, whereas they frequently reported that the MPA was better on slopes and uneven terrain. Conclusions: The 30° range of motion in the MPA can allow greater mobility when ambulating on typical environmental barriers (e.g., uneven terrain, ramps, and stairs) and allow patients to stand and walk on slopes with less socket discomfort. Most participants preferred the MPA. Frequently reported positive and negative aspects of both systems may be useful for patient consultation regarding ankle-foot technology. This study represents the largest known investigation of MPAs, and the results provide evidence of benefits from MPAs over ESAR feet in persons with UTA.